Biodecolourisation of palm oil mill effluent (POME) by selected exogenous bacteria - Mohd. Nazir, Nurain (2013)
Palm oil is now one of the top few edible oils in the world and will be leading player in the oil and fats market. However, palm oil mills generate large amount of by-product such as liquid effluent which requires effective management practices to minimize their negative impact on the environment. Palm Oil Mill Effluent (POME) is a highly polluted wastewater that pollutes the natural environment directly due to its high chemical oxygen demand (COD), biochemical oxygen demand (BOD), phenol and color concentration as well as unpleasant odors.This study was conducted to treat colour of final discharge POME using single bacterial culture. The processes being biological rely on suitable bacteria to break down the organic pollutants. The bacteria were originally isolated from palm oil mill sludge. The initial part of the research was selection of bacteria that can grow best in POME and screening the highest percentage of colour removal bacteria. Primary isolation is effected by streaking sample on the surface of agar containing nutrient broth and POME. The bacterium that showed the maximum reduction of colour was characterized from the genus Bacillus spp.via biochemical test. Parameters such as colour, COD, ammoniacal nitrogen, phenolic compound, lignin and pH were monitored. During the treatment, the maximum removal of colour was obtained up to 56% (2480 ADMI), COD removal of 26% (788 mg/L), ammoniacal nitrogen of 14% (42 mg/L), phenolic compound of 77% (56 mg/L) and lignin of 79% (25 mg/L) within 6 days. The pH of wastewater was in alkaline condition and increased from pH9.36 to pH9.59. In conclusion, biological treatment could potentially contribute in decolourisation of POME by using single bacteria itself.